2016
DOI: 10.3390/app6010008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Novel Thiazole-5-Carboxamide Derivatives

Abstract: A series of novel 2-phenyl-4-trifluoromethyl thiazole-5-carboxamide derivatives have been synthesized and evaluated for their anticancer activity against A-549, Bel7402, and HCT-8 cell lines. Among the tested compounds, highest activity (48%) was achieved with the 4-chloro-2-methylphenyl amido substituted thiazole containing the 2-chlorophenyl group on the two position of the heterocyclic ring. Other structurally similar compounds displayed moderate activity. The key intermediates have been fully characterized. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[6][7][8] Particularly, trifluoromethylated thiazoles have gained more attention in recent years. [9][10][11][12][13][14][15][16][17][18][19] This is probably because the biological activity of thiazoles can be modified by the incorporation of trifluoromethyl into their structure. [20][21][22] For example, 2-trifluoromethylthiazole-5-carboxamides GPS488 and GPS491 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Particularly, trifluoromethylated thiazoles have gained more attention in recent years. [9][10][11][12][13][14][15][16][17][18][19] This is probably because the biological activity of thiazoles can be modified by the incorporation of trifluoromethyl into their structure. [20][21][22] For example, 2-trifluoromethylthiazole-5-carboxamides GPS488 and GPS491 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that thiazole ring moiety appears almost in the commercialized antibiotics and antiparasitic such as acinitrazole, penicillin, nitazoxanide, aminitrozle and various synthetic drugs in markets [7,8,9]. Recent surveys showed that thiazole compounds play important role as antibacterial, anti-inflammatory, anticonvulsant and anticancer agents [10,11]. Structural activity relationship (SAR) study based on thiazole revealed that substituents on a particular position at position 2 and 4 of the 1,3-thiazole ring affect the biological behavior [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is an active unit in many drug molecules due to its property to bind with protein molecules [24]. Various heterocyclic moieties with amide functionality have displayed various potent biological activities as anti-cancer [25,26], anti-convulsant [27], anti-tubercular [28], anti-oxidant [29] and anti-inflammatory [30] activities. 'One-pot' synthesis of benzimidazole has gained much attraction in synthetic organic chemistry as it reduces the number of steps involved and the reaction time, and increases the yield of the product [31].…”
Section: Introductionmentioning
confidence: 99%